Can it be tuberculosis? A case series of atypical presentation of pulmonary tuberculosis - Khanduri, Rakhee Sodhi; Mason, Amita; Jethani, Varuna; Aggarwal, Ankit; Khanduri, Sushant; Kumar, Manoj (International Journal of Research in Medical Sciences, 2025)
Tuberculosis (TB) is a major health concern. It is a contagious disease caused by Mycobacterium tuberculosis. The disease can present in almost all sites-pulmonary and extrapulmonary. We always consider TB in our differentials. The commoner presentations are picked up early and treatment started promptly. However, when the presentation is atypical, diagnostic delays influence outcomes. We report six cases of pulmonary TB with varied radiological presentations. The findings include interstitial lung disease (ILD), malignancy, pulmonary infarction, tracheal thickening. All cases were diagnosed as TB after thorough invasive investigations, and successfully treated with anti-tubercular medication. Clinicians should be aware of atypical presentations of TB to ensure timely diagnosis and treatment.